2000
DOI: 10.1002/hep.510310129
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis drug-related liver dysfunction in chronic hepatitis B infection

Abstract: Liver toxicity is a common side effect of antituberculosis (anti-TB) drugs. We studied the differences in liver dysfunction observed during anti-TB treatment between hepatitis B virus carriers (HBV) and noncarriers. Three hundred twentyfour patients on anti-TB drugs were recruited and followed up for 1 year. Forty-three patients with HBV and 276 non-HBV patients were included for analysis. Liver function tests and viral markers were monitored monthly. Liver biopsy was requested whenever the alanine transaminas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
143
5
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(157 citation statements)
references
References 20 publications
(22 reference statements)
6
143
5
3
Order By: Relevance
“…Chronic hepatitis B and C is considered by some to enhance the risk of DILI particularly from drugs used to treat tuberculosis and HIV [73][74][75] ; however, not all studies have found a positive link between chronic B and C infection and anti-TB related DILI and highly active antiretroviral therapy related DILI. 76 Wong et al found hepatotoxicity following antituberculous drugs in 35% of HBV carriers in contrast to 9.4% non-carriers (p < 0.001).…”
Section: Hepatitis B and Hepatitis Cmentioning
confidence: 99%
“…Chronic hepatitis B and C is considered by some to enhance the risk of DILI particularly from drugs used to treat tuberculosis and HIV [73][74][75] ; however, not all studies have found a positive link between chronic B and C infection and anti-TB related DILI and highly active antiretroviral therapy related DILI. 76 Wong et al found hepatotoxicity following antituberculous drugs in 35% of HBV carriers in contrast to 9.4% non-carriers (p < 0.001).…”
Section: Hepatitis B and Hepatitis Cmentioning
confidence: 99%
“…55 Isoniazid monotherapy is safe in patients with HBV infection 56 while multidrug ATT is associated with significant incidence of hepatotoxicity. Multidrug therapy for tuberculosis is also associated with fulminant disease, increased mortality and later onset of hepatotoxic effects in these patients.…”
Section: Chronic Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Multidrug therapy for tuberculosis is also associated with fulminant disease, increased mortality and later onset of hepatotoxic effects in these patients. 55,57 Amongst 110 inactive HBsAg carriers and 97 controls without HBV infection, 38 inactive HBsAg carriers (35%) and 19 control subjects (20%) developed elevated liver enzyme levels during ATT (P = 0.016). 57 A higher proportion of inactive HBsAg carriers who received ATT evidenced moderate-to-severe drug-induced hepatotoxicity when compared with the control subjects (8 vs. 2%; P = 0.05).…”
Section: Chronic Hepatitis B Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations